The impact of modern information technology on the development of time measuring at the Olympic and Paralympic Games - Markovic, V.; Ratkovic, T.; Popovic, J.; Miloševic, M. (International Scientific Conference on Information Technology, Computer Science, and Data Science, 2024)
Timing in the Olympic Games is one of the most important aspects of professional sports` competitions which have evolved over time. Simple days of the Olympic Games with stopwatch as only technological device are long gone. Nowadays, there is the wide range of hi-tech time measuring devices, as well as hi-speed digital camera, electronic touchpad, new starting blocks, infrared beams and radio transmitters. This advanced IT equipment has replaced the human factor, thereby reducing the margin of error in time measurement to a minimum, which has enhanced the ranking of competitors in each race and match at the Olympic and Paralympic Games. The development of new timing technology makes it easier for spectators to follow the competition, improves their viewing experience, and helps coaches analyse the performances of their athletes.